Median nerve injury: an underrecognised complication of brachial artery cardiac catheterisation?. Issue 4 (1st October 1997) - Kennedy, Angus M; Grocott, Michael; Schwartz, Martin S; Modarres, Hamid; Scott, Mark; Schon, Fred
Abstract : OBJECTIVE: To describe the local neurological complications associated with cardiac catheterisation via the right brachial artery. METHODS: A follow up study to determine the mechanism of injury and outcome of patients who sustained a high median nerve palsy after this procedure. Five right handed patients were identified in a 24 month period. Each was assessed clinically and electrophysiologically at presentation. All were followed up initally (range six to 22 months) clinically, electrophysiologically, and using components from the Chessington occupational therapy neurological assessment battery (COTNAB) functional hand assessment. RESULTS: The incidence of this complication was between 0.2 and 1.4%. Three mechanisms of injury were identified. These included direct nerve compression due to formation of antecubital fossa haematoma, direct nerve trauma, and ischaemia secondary to brachial artery occlusion. The initial neurological and nerve conduction deficits improved with time. However, all cases had persistent disability in hand function as documented clinically and on the dexterity and stereognosis subcomponent of the COTNAB test. CONCLUSION: This is an uncommon, but probably underrecognised complication. Those performing cardiac catheterisation via the right brachial artery should be aware of the potential risks of damage to the median nerve. They should evaluate hand function after the procedure and take prompt action if median nerve dysfunction is noted. Damage to the median nerve results in appreciable long term disability, which may have medicolegal relevance.